1984
DOI: 10.1177/001872088402600608
|View full text |Cite
|
Sign up to set email alerts
|

A Job Severity Index for the Evaluation and Control of Lifting Injury

Abstract: Two large field studies were conducted to test the validity of the Job Severity Index (JSI) as an engineering tool for the control of manual materials-handling injury. Comparisons were made between the calculated JSIs of 453 individuals working in 101 different jobs and the injuries sustained by the same individuals over a period of 1057881 exposure hours (529 exposure years). The results revealed the existence of a job severity threshold above which the incidence, severity, and cost of injury dramatically inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 3 publications
0
39
0
Order By: Relevance
“…Twenty-seven studies met the inclusion criteria . On the basis of a screening of the references of the articles on these studies and recent reviews (9, l l ) , an additional 9 studies were included (94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). The selection of studies for inclusion, from a random sample (N=100) of the papers identified in Medline by the second reviewer, led to an initial 2% disagreement.…”
Section: Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven studies met the inclusion criteria . On the basis of a screening of the references of the articles on these studies and recent reviews (9, l l ) , an additional 9 studies were included (94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). The selection of studies for inclusion, from a random sample (N=100) of the papers identified in Medline by the second reviewer, led to an initial 2% disagreement.…”
Section: Selectionmentioning
confidence: 99%
“…The selection of studies for inclusion, from a random sample (N=100) of the papers identified in Medline by the second reviewer, led to an initial 2% disagreement. Five of the 36 selected studies were excluded post hoc for the following reasons: (i) there was low variability in physical load because the study population was restricted to workers with lifting tasks (50,51,95,98,99), (ii) the physical exposures at work were measured by means of a questionnaire on which only 1 of a list of items could be ticked (85), and (iii) the early retirements that were studied did not necessarily have a back disorder as the main diagnosis (25,26). Thus a total of 31 studies was finally included in this review, comprised of 28 cohort studies (27-49, 52-76, 78, 82-84, 86-94, 96, 97, 100, 102-104) and 3 case-referent studies (77,79-81, 101).…”
Section: Selectionmentioning
confidence: 99%
“…5,25,26 Occupational risk factors for low back injuries include manual handling tasks, 27 twisting, 28 bending, 28 falling, 29 reaching, 30 lifting excessive weights, 28,31,32 prolonged sitting, 29 and vibration. 28,33 Some nonoccupational risk factors for low back injury include obesity, 34 genetic factors, 35 and job satisfaction.…”
Section: Low Back Painmentioning
confidence: 99%
“…Surveillance of WRMDs (including the use of health-care-provider reports) can aid in identifying high-risk workplaces, occupations, and industries and in directing appropriate preventive measures. 11 Occupational risk factors for low back injuries include manual handling tasks, 12 twisting, 13 bending, 13 falling, 14 reaching, 15 lifting excessive weights, 13,16,17 prolonged sitting, 14 and exposure to vibration. 13,18 Some nonoccupational risk factors for low back injury include obesity, 19 genetic factors, 20 and job dissatisfaction.…”
Section: Work-related Musculoskeletal Disordersmentioning
confidence: 99%